2015
DOI: 10.1007/s00259-015-3074-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying [18F]fluorodeoxyglucose uptake in the arterial wall: the effects of dual time-point imaging and partial volume effect correction

Abstract: Purpose The human arterial wall is smaller than the spatial resolution of current positron emission tomographs. Therefore, partial volume effects should be considered when quantifying arterial wall 18 F-FDG uptake. We evaluated the impact of a novel method for partial volume effect (PVE) correction with contrast-enhanced CT (CECT) assistance on quantification of arterial wall 18 F-FDG uptake at different imaging timepoints. Methods Ten subjects were assessed by CECT imaging and dual time-point PET/CT imaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…CMV is defined as the volume within a given boundary determined using the FDG uptake threshold, such as the liver uptake and the blood pool [ 8 , 10 ]. However, as our study suggested, the liver uptake in CS patients was significantly increased from the time point before to that during steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…CMV is defined as the volume within a given boundary determined using the FDG uptake threshold, such as the liver uptake and the blood pool [ 8 , 10 ]. However, as our study suggested, the liver uptake in CS patients was significantly increased from the time point before to that during steroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the majority of LVV studies have been performed at 60 min, PET-positive criteria at delayed time points have not yet been evaluated in this setting and may differ slightly from those defined at the standard time interval. In contrast to FDG-PET studies evaluating metabolic activity of atherosclerotic lesions, studies comparing early (1 h) versus delayed (3 h) imaging in LVV are scarce [ 42 ]. A small prospective study in 23 patients with suspicion of LVV concluded that delayed imaging at 3 h yielded a more detailed image of the arterial wall, mainly due to decreased blood pool activity [ 43 ].…”
Section: Fdg-pet/ct(a) Procedures In Lvv and Pmrmentioning
confidence: 99%
“…The time interval between [ 18 F]FDG injection and scanning is critical if semiquantification using SUV is intended, but less important for visual reading only. Although the recommended interval is 60-90 min for cardiovascular imaging (similar to tumor imaging), 120-180 min is sometimes applied to help assess inflammatory activity in the vascular wall and left ventricle due to lower background activity in the blood pool (18,31,32), but these extended time-intervals seem less effective in infection detection (33). The regional acquisition time can be doubled for optimal visualization of small vascular structures, as with cranial and neck arteries in vasculitis (34).…”
Section: Specific Patient Preparation Non[ 18 F]fdg Radiopharmaceuticalsmentioning
confidence: 99%